Emergent Nested Systems A Theory of Understanding and Influencing Complex Systems as well as Case Studies in Urban Systems - Walloth, Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a theory as well as methods to understand and to purposively influence complex systems. It suggests a theory of complex systems as nested systems, i. e. systems that enclose other systems and that are simultaneously enclosed by even other systems. According to the theory presented, each enclosing system emerges through time from the generative activities of the systems they enclose. Systems are nested and often emerge unplanned, and every system of high dynamics is enclosed by a system of slower dynamics. An understanding of systems with faster dynamics, which are always guided by systems of slower dynamics, opens up not only new ways to understanding systems, but also to effectively influence them. The aim and subject of this book is to lay out these thoughts and explain their relevance to the purposive development of complex systems, which are exemplified in case studies from an urban system. The interested reader, who is not required to be familiar with system-theoretical concepts or with theories of emergence, will be guided through the development of a theory of emergent nested systems. The reader will also learn about new ways to influence the course of events - even though the course of events is, in principle, unpredictable, due to the ever-new emergence of real novelty.
Complex Systems and Man's Desire to Understand and Influence Them -- A Theory of Emergent Nested Systems -- Understanding and Influencing Emergent Nested Systems -- Reflections and Outlook.
Keywords: Dynamics; Nonlinear theories; System theory; Nonlinear Optics; Sociology, Urban; Applied Dynamical Systems; Complex Systems; Nonlinear Optics; Urban Sociology